Journalism training aid by Australians: A case study in the Solomon Islands - Wake, Alexandra (Pacific Journalism Review, 2016)
After the ethnic clashes and generally poor plight of Solomon Islands at the turn of the millennium, the country has been the recipient of substantial international foreign aid, which has included journalism education and training, particularly from Australia. However, little independent research has been done about the role of Australian trainers and the history of journalism training in this period of change and restoration. This article seeks to provide a point-in-time report on journalism training in an aid context, in a bid to provide a baseline for future investigation of changes in the media landscape and training in Solomon Islands. This research draws on independent in-depth interviews with engaged stakeholders in the Solomon Islands, including journalists, civil leaders and government figures. It also discusses the Australian government-funded media aid programmes, including the Solomon Islands Media Assistance Scheme (SOLMAS) and its unnamed predecessor.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjQxMzUvcGpyLnYyMmkyLjY4